2021
DOI: 10.1002/cpt.2222
|View full text |Cite
|
Sign up to set email alerts
|

NT‐proBNP Qualifies as a Surrogate for Clinical End Points in Heart Failure

Abstract: N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a well-established biomarker in heart failure (HF) but controversially discussed as a potential surrogate marker in HF trials. We analyzed the NT-proBNP/mortality relationship in real-world data (RWD) of 108,330 HF patients from the IBM Watson Health Explorys database and compared it with the NT-proBNP / clinical event end-point relationship in 20 clinical HF studies. With a hierarchical statistical model, we quantified the functional relationship and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 51 publications
4
19
0
Order By: Relevance
“…While drug-induced effects on natriuretic peptides may not always reflect effects on clinical endpoints, we have demonstrated that, after short treatment durations of less than 10 weeks, NT-proBNP levels predict hazard ratios with confidence levels comparable to the final trial readout [39]. Interestingly, the effect of vericiguat on top of SoC was not linear, but dependent on [NT-proBNP] baseline as an indicator of disease severity and cardiac wall stress (Fig.…”
Section: All Patientsmentioning
confidence: 79%
See 1 more Smart Citation
“…While drug-induced effects on natriuretic peptides may not always reflect effects on clinical endpoints, we have demonstrated that, after short treatment durations of less than 10 weeks, NT-proBNP levels predict hazard ratios with confidence levels comparable to the final trial readout [39]. Interestingly, the effect of vericiguat on top of SoC was not linear, but dependent on [NT-proBNP] baseline as an indicator of disease severity and cardiac wall stress (Fig.…”
Section: All Patientsmentioning
confidence: 79%
“…While drug-induced effects on natriuretic peptides may not always reflect effects on clinical endpoints, we have demonstrated that, after short treatment durations of less than 10 weeks, NT-proBNP levels predict hazard ratios with confidence levels comparable to the final trial readout [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is an urgent need to find a new risk stratification marker in addition to LVEF and NYHA. Since published data have shown that NT-proBNP has a close relationship with all-cause mortality (15,16), pump failure death (15,16), and sudden death in a variety of populations (21)(22)(23)(24)(25)(26)(27), it is also expected to be a promising marker for HF with ICD.…”
Section: Discussionmentioning
confidence: 99%
“…It is an established biomarker of HF diagnosis and prognosis (15,16). Moreover, it is recognized as a surrogate indicator for all-cause mortality, HF hospitalization, and HF death (16). In addition, it is associated with myocardial fibrosis (17), which is a wellestablished arrhythmogenic substrate (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation